Capillary Nanostamping with Spongy Mesoporous Silica Stamps. (18th April 2018) - Schmidt, Mercedes; Philippi, Michael; Münzner, Maximilian; Stangl, Johannes M.; Wieczorek, René; Harneit, Wolfgang; Müller‐Buschbaum, Klaus; Enke, Dirk; Steinhart, Martin
Abstract: Classical microcontact printing involves transfer of molecules adsorbed on the outer surfaces of solid stamps to substrates to be patterned. Spongy mesoporous silica stamps are prepared that can be soaked with ink and that are topographically patterned with arrays of submicron contact elements. Multiple successive stamping steps can be carried out under ambient conditions without ink refilling. Lattices of fullerene nanoparticles with diameters in the 100 nm range are obtained by stamping C60 /toluene solutions on perfluorinated glass slides partially wetted by toluene. Stamping an ethanolic 1‐dodecanethiol solution onto gold‐coated glass slides yields arrays of submicron dots of adsorbed 1‐dodecantethiol molecules, even though macroscopic ethanol drops spread on gold. This outcome may be related to the pressure drop across the concave ink menisci at the mesopore openings on the stamp surface counteracting the van der Waals forces between ink and gold surface and/or to reduced wettability of the 1‐dodecanethiol dots themselves by ethanol. The chemical surface heterogeneity of gold‐coated glass slides functionalized with submicron 1‐dodecanethiol dots is evidenced by dewetting of molten polystyrene films eventually yielding ordered arrays of polystyrene nanoparticles. Abstract : Silica stamps containing continuous spongy mesopore systems and contact surfaces topographically patterned with contact elements are used for capillary nanostamping under ambient conditions. Ink can be supplied anytime to the contact surface through the mesopore system. Thus, regular arrays of fullerene nanoparticles and of sub‐micrometer alkylthiol dots are stamped.